2017
DOI: 10.1007/s00595-017-1592-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the prognostic factors in patients with pT3N0 or pT1N2–3 gastric cancer: a single institutional retrospective cohort study

Abstract: The prognosis of pT3N0/pT1N2-3 gastric cancer patients treated by surgery alone was relatively good; however, patients with pathological vessel infiltration may be at high risk of recurrence and could be candidates for adjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…We included the tumor diameter as a continuous variable, which improved the reliability of the results. Previous studies have revealed that pT3N0 GC patients with vascular infiltration have a higher risk of tumor recurrence[ 6 - 8 ], indicating a poor prognosis, which was not consistent with our findings. In fact, determination of the presence or absence of postoperative vascular infiltration may vary due to different staining methods and diagnostic criteria between single centers[ 31 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We included the tumor diameter as a continuous variable, which improved the reliability of the results. Previous studies have revealed that pT3N0 GC patients with vascular infiltration have a higher risk of tumor recurrence[ 6 - 8 ], indicating a poor prognosis, which was not consistent with our findings. In fact, determination of the presence or absence of postoperative vascular infiltration may vary due to different staining methods and diagnostic criteria between single centers[ 31 ].…”
Section: Discussioncontrasting
confidence: 99%
“…According to the results of the ACTS-GC trial[ 3 ], the indications for postoperative chemotherapy excluded pT1N2-3 patients who were classified as stage II/III due to pT1 and pT3N0 patients who were classified as stage IB based on the 13 th edition of the Japanese Classification of Gastric Carcinoma[ 16 ]. And in the current 14 th edition, pT3N0 patients were classified as stage IIA[ 6 ]. However, there are still patients with pTIN2-3 and pT3N0 GC who have a poor prognosis, and identifying them through a clinical retrospective study is of substantial value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 In practice, the 5-year OS of T1N1M0/T2N0M0 patients is nearly 90% by surgery alone. 28,29 Poor survival outcome of T1N1M0/ T2N0M0/T3N0M0 has been associated with lymphatic invasion, wide (>1.5 cm) submucosal invasion, and venous invasion [30][31][32][33] ; however, the fraction of patient positive with these factors seemed too high to stratify potentially-relapse patients. 30,33 In practice, T1N1M0/T2N0M0/ T3N0M0 cases treated with "adjuvant" chemotherapy in clinical practice had a better OS, 34 although one could postulate that approximately 90% of patients treated should not have benefited from the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Poor survival outcome of T1N1M0/ T2N0M0/T3N0M0 has been associated with lymphatic invasion, wide (>1.5 cm) submucosal invasion, and venous invasion [30][31][32][33] ; however, the fraction of patient positive with these factors seemed too high to stratify potentially-relapse patients. 30,33 In practice, T1N1M0/T2N0M0/ T3N0M0 cases treated with "adjuvant" chemotherapy in clinical practice had a better OS, 34 although one could postulate that approximately 90% of patients treated should not have benefited from the treatment. Our presenting observation shows that TP53 codon 72 Pro/Pro polymorphisms may therefore effectively identify T1N1M0/ T2N0M0/T3N0M0 patients who would benefit from postoperative adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%